Classification of biological and bioinspired aquatic systems: A review. (15th January 2018) - Salazar, R.; Fuentes, V.; Abdelkefi, A.
Abstract: Robotic systems capable of aquatic movement has increased exploitation in recent years due to the diverse range of missions that can be performed in otherwise hostile environments. These aquatic unmanned vehicles (AUVs) have begun to transition to systems that replicate biological animals as they are already extremely efficient at moving in aqueous environments. The result is the abandonment of inefficient propeller based locomotion for a biological locomotion type suitable for the specific mission. There is a diverse range of biological locomotion's available with animals that give a range of criteria to follow. In this review, existing aquatic animals and found AUVs are classified. How the bioinspired systems compare to the animals in their locomotion is investigated and discussed. Then, it is discussed what makes these systems bioinspired and biomimetic, and the AUVs that fall into these distinctive categories. Limitations and future recommendations on possible improvements for these systems are offered. Highlights: Existing aquatic animals and found AUVs are reviewed and classified. How the bioinspired systems compare to the animals in their locomotion is investigated and discussed. What makes these systems bioinspired and biomimetic, and the AUVs that fall into these distinctive categories is consolidated. Limitations and future recommendations on possible improvements for these systems are offered.